Duša v Kafkovi "Preobrazbi" - Snoj, Vid (Primerjalna književnost, 2012)
This paper deals with the issue of what happens to the main hero's soul in Kafka's famous story that begins with his physical transformation. It portrays some kind of a hunt for the soul that does not even explicitly appear in the story.
Keywords: Kafka, Franz, 1883-1924; nemška književnost; German-language literature; judovska mistika; duša; preobrazba